Gene sequence and the 1.8 Å crystal structure of the tungsten-containing formate dehydrogenase from Desulfovibrio gigas - Raaijmakers, Hans (2019)
This work was supported by EC-TMR/FMRX-CT980204, PhD grant PRAXISXXI/BD/16009/98 (S.M.), and PhD grant PRAXISXXI/BD/13530/97 (J.M.D.). We thank the EMBL Grenoble Outstation, beamline BM-14, for MAD measurements at the ESRF under the European Union TMR/LSF Program. Hans Bartunik and Gleb Bourenkov are acknowledged for help at the BW6 beamline of the MPG-ASMB in DESY, Hamburg, for collecting the first FDH native data set. The Institute for Genomic Research (TIGR) is kindly acknowledged for making the preliminary sequence data on the Desulfovibrio vulgaris Hildenborough genome available to the public at their Website ( http://www.tigr.org ).